Pengembangan Roadmap Penelitian Bahasa dan Sastra Fakultas Bahasa dan Seni Universitas Negeri Surabaya - Giri, Ephrillia Noor Fitriana; Mukhzamilah; Respati Retno Utami; Wisma Kurniawati; Sumarniningsih; Hespi Septiana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to compile a Roadmap for Language and Literature research in the 2016-2025 period and to predict lecturers' interest in research in the field of Language and Literature in accordance with the vision and mission of the study program and UPPS. This research refers to the results of research policy documents at the faculty and university levels, as well as documents of achievement of policies that have been previously determined. The FGD method is directed at reviewing existing documents. The analytical method used in this research is secondary data analysis or existing statistics. The results of this study are that in the next 10 years, the previous 5 years 2016-2020 represent basic research, the next 5 years 2021-2025 are development research. The priority topics that can become the umbrella for the Language and Literature research roadmap of FBS Surabaya State University for the 2016-2025 period are elaboration of Microlinguistics, Macrolinguistics, Literary Studies, Curriculum Studies, Learning, Literacy, Entrepreneurship for 2016-2020. This can be interpreted that the lecturers have implemented an efficient learning system that supports the careers of graduates later.